2022
DOI: 10.1186/s40550-022-00099-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment and risk characterization of aflatoxins intake through consumption of maize (Zea mays) in different age populations in the Volta Region of Ghana

Abstract: Aflatoxin contamination in foods is a vital health challenge for low and middle-income countries in subtropical regions. Maize (Zea mays L.), a staple food most widely grown in Africa including Ghana, and extensively consumed as much as three times per day, is a source of aflatoxin contamination owing to its susceptibility to fungal infection. Aflatoxin levels were checked against international (European Commission, EC) and local (Ghana Standards Authority, GSA) standards, and health risks associated with maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The MOE values found in this study are comparable to those reported in some African countries; Studies from Kenya, Botswana, Gambia and Tanzania reported MOE values of 6.5, 37.8, 621.7 and 202 respectively (Shephard et al, 2008). Similarly AFB1 Margin of Exposure (MOE) values of 6.80, and 6.75 for children and adults were recorded for a study on maize consumption in Ghana (Kortei et al, 2022). Exposure assessment and estimated cancer risk due to consumption of maize grains from related studies in Nigeria showed much higher risk than the current study; MOE values in the range of 0.01-0.54 and 0.02 -1.30 were reported for children and adult groups respectively in a study on risk assessment of mycotoxins in stored maize grains consumed by infants and young children in Nigeria (Adetunji et al, 2017).…”
Section: Figure 1 Comparison Of Afb1 Levels In Groundnut Samples From...supporting
confidence: 83%
“…The MOE values found in this study are comparable to those reported in some African countries; Studies from Kenya, Botswana, Gambia and Tanzania reported MOE values of 6.5, 37.8, 621.7 and 202 respectively (Shephard et al, 2008). Similarly AFB1 Margin of Exposure (MOE) values of 6.80, and 6.75 for children and adults were recorded for a study on maize consumption in Ghana (Kortei et al, 2022). Exposure assessment and estimated cancer risk due to consumption of maize grains from related studies in Nigeria showed much higher risk than the current study; MOE values in the range of 0.01-0.54 and 0.02 -1.30 were reported for children and adult groups respectively in a study on risk assessment of mycotoxins in stored maize grains consumed by infants and young children in Nigeria (Adetunji et al, 2017).…”
Section: Figure 1 Comparison Of Afb1 Levels In Groundnut Samples From...supporting
confidence: 83%
“…[ 25 ] investigated aflatoxins in commercial poultry feed in Cameroon and reported aflatoxins levels ranging from 2 to 42 μg/kg for maize, which is similar to total aflatoxin levels of 2.5–54.26 μg/kg recorded for maize in the present study. Also [ 21 ], reported total aflatoxins levels of 1.89 − 444.01 μg/kg for maize sampled from Volta region, Ghana. In addition [ 29 ], investigated aflatoxin prevalence in maize sampled from different ecological zones in Ghana and reported total aflatoxins ranging from 1 to 341 μg/kg for maize.…”
Section: Resultsmentioning
confidence: 99%
“…Nakavuma et al [ 20 ] evaluated the knowledge of mycotoxins and the incidence of aflatoxins in chicken diets and feed components in various locations of Uganda, they reported a total aflatoxin concentration ranging from 6.79 to 412.59 g/kg. More recently [ 21 ] investigated aflatoxin levels in maize sampled from Volta region in Ghana and reported total aflatoxins level ranging from 1.89 to 444.01 μg/kg. Also [ 22 ], reported total aflatoxins level of 1.0–4.61 μg/kg for wheat bran.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 100 samples analyzed for total aflatoxins (total AFs), 68 (68%) exceeded the limits set by the EC, with concentration ranges of 4.98 ± 0.6-445.01 ± 8.9 μg/kg. Similarly, 58 (58%) of the samples exceeded the limits set by GSA, with concentration ranges of 12.12 ± 1.4-445.01 ± 8.9 μg/kg [26].…”
Section: The Carcinogenic Properties Of Aflatoxins B 1 B 2 G 1 and Gmentioning
confidence: 86%